1999
DOI: 10.1046/j.1365-2036.1999.00001.x-i1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of racecadotril and loperamide on bacterial proliferation and on the central nervous system of the newborn gnotobiotic piglet

Abstract: Methods The effects of 4 days of oral administration of different doses of two drugs, an enkephalinase inhibitor (the antisecretory agent, racecadotril) and a μ‐receptor agonist (loperamide), on intestinal growth of a bacterial nonpathogenic strain (Escherichia coli E 404) and on the central nervous system (CNS) were compared in newborn gnotobiotic piglets. Results The E. coli content of the proximal jejunum (segment S1) and the E. coli ratio of stomach:segment S1 were similar in the racecadotril (20 mg/kg b.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 21 publications
0
33
0
Order By: Relevance
“…The anatomy of the GI remnant can be a primary driver of bacterial overgrowth. For example, patients with blind loops or small‐bowel dilation have reduced intestinal motility, which can result in stagnation of intestinal contents and promote local bacterial fermentation 23 , 53 . Patients with resections that include removal of the terminal ileum and/or ileocecal valve may experience migration of anaerobic colonic bacteria into the small intestine because of a breakdown of this anatomical transition zone 54 .…”
Section: Bacterial Overgrowthmentioning
confidence: 99%
See 1 more Smart Citation
“…The anatomy of the GI remnant can be a primary driver of bacterial overgrowth. For example, patients with blind loops or small‐bowel dilation have reduced intestinal motility, which can result in stagnation of intestinal contents and promote local bacterial fermentation 23 , 53 . Patients with resections that include removal of the terminal ileum and/or ileocecal valve may experience migration of anaerobic colonic bacteria into the small intestine because of a breakdown of this anatomical transition zone 54 .…”
Section: Bacterial Overgrowthmentioning
confidence: 99%
“…Patients with resections that include removal of the terminal ileum and/or ileocecal valve may experience migration of anaerobic colonic bacteria into the small intestine because of a breakdown of this anatomical transition zone 54 . Finally, medications commonly prescribed to patients with SBS, including antimotility agents and acid‐suppressing therapies, have the potential to disrupt normal bacterial flora and permit overgrowth 23 , 53 …”
Section: Bacterial Overgrowthmentioning
confidence: 99%
“…[26] Noteworthy, racecadotril does not induce reactive constipation [27] and does not promote small bowel bacterial overgrowth, [28] actions exhibited by a widely used loperamide. Racecadotril, inhibitor of neprilysin, is an antidiarrheal agent which acts without modifying the basal absorption of water and electrolytes and with no impact on intestinal transit.…”
Section: Resultsmentioning
confidence: 99%
“…The antisecretory mechanisms are independent of effects on intestinal motility, differentiating this compound from μ-opiate receptor agonists like loperamide and diphenoxylate. Experimental studies in rodents and human volunteers demonstrated no delay on gastrointestinal transit or increase in experimental bacterial proliferation in small bowel of germ free piglets with racecadotril as compared to loperamide [5].…”
Section: Pharmacological Propertiesmentioning
confidence: 90%